Englisia - Universitas Islam Negeri Ar-Raniry. Prodi Pendidikan Bahasa Inggris (Department of English Language Education (Prodi Pendidikan Bahasa Inggris), Fakultas Tarbiyah dan Keguruan (Faculty of Education and Teacher Training), 2013)
Language studies in English language teaching and various other related applied linguistics themes. The journal publishes articles of interest to language teachers, practitioners and language researchers.
Keywords: English language : Study and teaching : Periodicals; English language : Study and teaching : Indonesia : Periodicals; English language : Study and teaching; Indonesia